Sustaining Democratic Rule In Nigeria: The Corruption Tide - Asaju, Kayode (Advances in Social Sciences Research Journal, 2014)
Democratic governance is the most popular form of government that appeals to the people because of it underlying principles which are people-centered. Seeing its successful operation in the West, many developing countries including Nigeria adopts it in the 1960s. However, sustaining this hard-earned democracy has been a very big hurdle due to corruption. Corruption has been the major cog on the wheels of democratic rule in Nigeria. Suffice it to say that democracy in the First, Second and Third Republic collapsed due to widespread official corruption among the ruling class. It is ostensibly believed among the ruling class that Nigeria is now in a democratic dispensation but corruption has robbed the citizens of democratic benefits. This has thrown the political system into legitimacy crises. Hence, corruption has been identified as the major threat to sustainable democratic rule because it has become more endemic and prevalent among not only the leaders but also the followers. Using secondary data, the paper examines the negative relationship between democracy and corruption; by so doing, it reflects on the various manifestations and classification of corruption; it further examine the effects of corruption on democratic governance and posits that despite several efforts of government in fighting corruption, the scourge is still prevalent, even more in the public institutions that should enhance the successful crusade, because of lack of genuine political-will to combat corruption. The paper therefore, recommends genuine political-will, especially on the part of the government to take proactive steps in fighting corruption; exemplary leadership style; intensifying anti-corruption studies at all educational levels among others as ways of ensuring corrupt-free sustainable democracy in Nigeria.